Understanding university students’ behavioral intention to use Edmodo through the lens of an extended technology acceptance model - Unal, Erhan; Uzun, Ahmet Murat (British journal of educational technology, 2021)
Educational social network sites have many uses in the field of education. The present paper aims to determine factors influencing students’ behavioral intention to use a popular educational social network site, Edmodo. Using an extension of the technology acceptance model, we analyzed quantitative responses of 218 university students, registered in an Edmodo supported course. Data were analyzed through partial least squares structural equation modeling. Results highlighted that intention was significantly predicted by its antecedents. More specifically, the attitude was the most important factor, whilst perceived usefulness had a moderate impact on predicting intention. Perceived ease of use predicted perceived usefulness directly and also it influenced intention indirectly through attitude. External antecedents of perceived usefulness and perceived ease of use were all significant. Discussion and implications were drawn based on the results. Practitioner Notes What is already known about this topic Understanding why users accept or reject a particular information system is a common research area. Technology acceptance model (TAM) is used to explain individuals’ acceptance and adoption of different technologies. Social Networking Sites (SNSs) have been used to enrich learning. However, the adoption of educational SNS studies is limited. What this paper adds This study is one of the first attempts for employing extended TAM that scrutinizes factors influencing university students’ intention to use Edmodo as an educational SNS and a learning management system (LMS) in teaching and learning environments. External antecedents included in the model (subjective norms, output quality, perceptions of external control, perceived enjoyment, technological complexity, and self‐efficacy) significantly predicted university students’ intention to use Edmodo as an educational SNS and LMS. Major factors driving the intention to use Edmodo were attitude and perceived usefulness. Implications for practice and/or policy Considering that the attitude was found to have the strongest influence on the intention to use Edmodo, instructors may attach prominent importance to foster students’ positive attitudes toward Edmodo use. Instructors may design virtual learning environments with collaborative activities on SNS to increase students’ perceived usefulness. Designers and developers of an educational SNS should design interfaces that should be not only less complex but also more enjoyable.